2015
DOI: 10.1097/mot.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Overview of pediatric organ transplantation

Abstract: It is important to generate registries of pediatric patients with organ transplantation for conducting observational studies, which might provide information for designing future RCTs and new insights toward improving the survival rates and long-term predictors of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Our group recently published a review that concluded, based on 2 published studies [ 33 , 61 ], that a maximum total rATG dose of 7.5 mg/kg is adequate in children at standard immunological risk receiving CNI-based maintenance therapy [ 13 ]. A lower cumulative dose (but not less than 3.5 mg/kg) may be sufficient in younger, lower-risk patients who are receiving CNI therapy, in view of the increased risk for PTLD in the youngest recipients [ 8 , 13 ], although this has not been assessed clinically. The duration of rATG infusion should not be less than 6 h [ 13 ].…”
Section: Ratg Dosing and Monitoring In Pediatric Heart Transplantatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Our group recently published a review that concluded, based on 2 published studies [ 33 , 61 ], that a maximum total rATG dose of 7.5 mg/kg is adequate in children at standard immunological risk receiving CNI-based maintenance therapy [ 13 ]. A lower cumulative dose (but not less than 3.5 mg/kg) may be sufficient in younger, lower-risk patients who are receiving CNI therapy, in view of the increased risk for PTLD in the youngest recipients [ 8 , 13 ], although this has not been assessed clinically. The duration of rATG infusion should not be less than 6 h [ 13 ].…”
Section: Ratg Dosing and Monitoring In Pediatric Heart Transplantatiomentioning
confidence: 99%
“…The youngest children (<6 years) have a lower risk for early or late acute rejection than do older children [ 2 ], while those aged more than 6 years show similar rates of rejection to those of younger adults [ 2 ]. Over-immunosuppression should be avoided in infants due to the higher risk of post-transplant lymphoproliferative disorder (PTLD) than in adults [ 2 , 8 ]. Lastly, the imperative to minimize long-term metabolic complications such as post-transplant diabetes mellitus (PTDM) is more pressing in children, since they will require immunosuppression for many decades, with the additional need to ensure that growth is as normal as possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After transplantation, immunosuppressants become a necessity. Life-long surveillance is needed to detect and diagnose potential problems, such as infections and tumours (Malik et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Organ transplantation is a life-saving procedure for children suffering from end-stage organ diseases ( 1 ). Immunosuppressive therapy is necessary to prevent the rejection of transplanted organs in children; However, this therapeutic approach renders them highly susceptible to infections ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%